Dakwah Muamalah Dalam Islam - Rofiki Rofiki; Faridatul Jannah; Desi Endang Maisuri (STAI Publisistik Thawalib Jakarta, 2023)
The aim of this research is to explain and describe the da'wah of mualamah in Islam. The research was conducted qualitatively through library research. Data collection was carried out by means of a documentation study using books, books, the internet, and so on. Data processing with reduction, presentation, and conclusion. The results of the study showed: (1) aspects of da'wah: mad'u abilities, geographic location, materials, and tools of da'wah. (2) muamalah aspects: contracts, liking each other, and goods sold are beneficial. (3) Da'wah mulamalah about: capital, honesty, punctuality, hard work, hard work, and motivating the closest people.